Provimento de cargo de diretores de escolas públicas de ensino fundamental - Gonçalves, Amanda (2019)
This work sought to understand the discourses about the process of filling a position of municipal school director in municipal laws of three municipalities in the interior of. (Araçatuba, Barretos and Franca). Since municipalities can choose the form of provision, there are some models provided by the municipal school director, the appointment or appointment (performed by the mayor or municipal secretary of education), election (carried out by the school community (here the management team, the parents, the students and the community) and public competition (evidence and analysis of titles). Some questions have become a hypothesis: To what extent does the form of filling a position of school director contained in the official documents generate discourse effects? The research in question is of a documentary nature and focused on the determination of the following theoretical categories: relations of power in the institutions and provision of office of Michel Foucault's theories. The same author was used in based on Discourse Analysis. Documents used in the public and online domain were used. The selection of the municipalities in which we seek the data for the development of the research was based on the division created by the IBGE as "Administrative Regions" being these seventeen regions, from each administrative region were chosen municipalities with a total of 500 thousand inhabitants (median municipality). To dilute the locations in the State of São Paulo, totaling nine cities and finally three cities of the nine previously mentioned were selected: Araçatuba, Barretos, Franca. Data were available on legislation accessible through the internet, in the public domain, and were therefore sufficient to carry out this dissertation and to cover the stated objective. There is a large amount of data available which has made us reduce the selection so that the objectives of the research were met, considering that further research will be necessary to analyze all this data.